Evaluation of 880 patients diagnosed with acute pancreatitis according to the Revised Atlanta Classification: A single-center experience - Binicier,Omer Burcak (2020)
SUMMARY OBJECTIVE The Revised Atlanta Classification (RAC) is increasingly used in the evaluation of patients diagnosed with acute pancreatitis (AP). In our study, we aimed to evaluate the etiology, disease severity, and mortality rates of patients diagnosed with AP in our center in the previous 6 years. METHODS Patients diagnosed with AP between 2013 and 2018 were evaluated. AP etiology, demographic data, disease severity, and mortality rates according to the RAC were evaluated. RESULTS A total of 880 patients were included in the study. Five hundred and eighteen (59%) patients were female and 362 (41%) were male. Regarding the etiology, 474 (53.9%) patients had biliary AP (BAP), 71 (8.1%) had hyperlipidemic AP (HAP), and 44 (5%) had alcoholic AP (AAP). According to the RAC, 561 (63.7%) patients were considered to be in the mild AP group (MAP), 268 (30.5%) in the moderately severe AP (MSAP), and 51 (5.8%) in the severe AP (SAP). The mortality rate was 4.8% in the MSAP group and 49% in the SAP group. Mortality was 2.3 times in patients over 65 years old and 3.7 times higher in patients with ischemic heart disease. CONCLUSIONS In our country, BAP is still the main etiology of acute pancreatitis. Over the years, we have seen a decrease in BAP and idiopathic AP cases, while there was an increase in HAP cases due to factors such as lifestyle changes and fatty nutrition. We found that mortality was associated with disease severity, advanced age (> 65 y), hypertension, and ischemic heart disease regardless of the etiology.